2024
DOI: 10.3390/ani14020272
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance, Blood Metabolites and Carcass Characteristics of Black Goat Kids Fed Diets Containing Olive Cake

Belal S. Obeidat,
Milton G. Thomas

Abstract: This study investigated the dietary effect of incorporating different levels of olive cake (OC) on the metabolic responses, growth performance, and carcass characteristics of black goat male kids. Thirty kids (body weight = 17.3 ± 0.40 kg) were randomly distributed into one of three equally sized dietary groups: a control diet (CON), OC at 75 g/kg (OC75), and OC at 150 g/kg (OC150) of dietary dry matter (DM). The results revealed that the intake of DM, crude protein (CP), neutral detergent fiber (NDF), and aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…As conventional imported feed ingredients may negate profit margins for sheep, livestock producers have begun to search for alternative feeds at lower costs [ 3 ]. This research program conducted a series of experiments and found that the use of alternative feeds decreases the cost of production without impacting the health status of small ruminants [ 2 6 ]. Feeding by-products from local sources, such as pomegranate seed pulp (PSP) and coconut meal (COC), to livestock can reduce the cost of milk production and increase profits.…”
Section: Introductionmentioning
confidence: 99%
“…As conventional imported feed ingredients may negate profit margins for sheep, livestock producers have begun to search for alternative feeds at lower costs [ 3 ]. This research program conducted a series of experiments and found that the use of alternative feeds decreases the cost of production without impacting the health status of small ruminants [ 2 6 ]. Feeding by-products from local sources, such as pomegranate seed pulp (PSP) and coconut meal (COC), to livestock can reduce the cost of milk production and increase profits.…”
Section: Introductionmentioning
confidence: 99%